Etika Interaksi Edukatif Guru dan Murid Menurut Perspektif Syaikh ʻAbd Al-Ṣamad Al-Falimbānī - Suriadi Suriadi (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
Ethics is the main pillar in building the humans’ life order. One cannot survive, and education cannot stand upright and firm without being supported by good and noble ethical values. Nowday world has witnessed the crisis of ethics, awakening us all to fix it, starting from at least ourselves. This study aimed at figuring out the ethics of teachers and students in the book of Sīrus al-Sālikīn by Syaikh'Abd al-Ṣamad al-Falimbānī and its relevance in the current educational context. The study used library research or literature study with descriptive approach. Primary and secondary data were obtained through literature research through documentation method. The data were then analyzed by using content analysis technique. The results of the study showed that Syaikh 'Abd al-Ṣamad al-Falimbānī revealed that the teacher ethics was more important than the other factors, and thushe provided strict ethics for the teachers. In addition, the students should always hold on to the noble ethics in interacting with the teachers, both in the process of teaching and learning and in everyday life. In general, the ethics theory put forward by Syaikh 'Abd al-Ṣamad al-Falimbānī is still highly relevant and applicable in the context of current learning.